2006
DOI: 10.2119/2005-00046.hewett
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of the Human tie-1 Promoter with Triplex-Forming Oligonucleotides Targeted to Ets Binding Sites

Abstract: The Tie receptors (Tie-1 and Tie-2/Tek) are essential for angiogenesis and vascular remodeling/integrity. Tie receptors are upregulated in tumor-associated endothelium, and their inhibition disrupts angiogenesis and can prevent tumor growth as a consequence. To investigate the potential of anti-gene approaches to inhibit tie gene expression for anti-angiogenic therapy, we have examined triple-helical (triplex) DNA formation at 2 tandem Ets transcription factor binding motifs (designated E-1 and E-2) in the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…3B). This finding is consistent with another study that found that mutation of Ets sites in the human Tie1 promoter also had an immense effect on its activity [14]. Therefore, Ets-binding sites should be conserved in endothelium-specific gene expression, and it is necessary for a promoter or an enhancer to improve transcription.…”
Section: Site-directed Mutagenesis Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…3B). This finding is consistent with another study that found that mutation of Ets sites in the human Tie1 promoter also had an immense effect on its activity [14]. Therefore, Ets-binding sites should be conserved in endothelium-specific gene expression, and it is necessary for a promoter or an enhancer to improve transcription.…”
Section: Site-directed Mutagenesis Analysissupporting
confidence: 91%
“…The activity and specificity of the mouse Tie1 promoter have been confirmed and used to study vascular development . Several putative transcription‐factor‐binding sites in endothelial cell‐specific promoters have been identified, including AP2, GATA, Ets, and Oct1, which regulate specific gene expression in endothelial cells . However, the porcine Tie1 promoter has not been identified and used for genetic modification.…”
Section: Introductionmentioning
confidence: 99%
“…TFOs have been shown in vitro to alter gene expression during the transcription process (Figure 5A and B), by interfering either with the binding of transcription factors (94,95) or with the formation of the initiation complex (96). It can also arrest transcription elongation by binding to the transcribed position of the targeted gene (97).…”
Section: In Vitro Applications Of Tfos As Gene Modulatorsmentioning
confidence: 99%
“…A recent example of inhibition of transcription by triplex strategy has been reported on tie-1 promoter, where the formation of a stable triplex prevents the binding of Ets transcription factors that are essential for the promoter activity (94). In this case, PS TFOs inhibit promoter activity and tie1 expression in vitro and in endothelial cells.…”
Section: In Vitro Applications Of Tfos As Gene Modulatorsmentioning
confidence: 99%
“…Triplex forming ONs (TFOs) can bind to the major groove of the DNA double helix, which has been explored in different applications, such as transcriptional activation (72), blocking of transcription (73)(74)(75)(76), recruitment of transcription factors (77,78), fluorescent in situ hybridization of repetitive chromosomal regions (79) and TFO-padlock mediated tagging of DNA fragments (80). TFOs can even bind to DNA at transcriptionally silent loci, however, binding was dramatically increased upon targeting actively transcribed genes (81,82).…”
Section: Anti-gene Oligonucleotidesmentioning
confidence: 99%